The association between daily movement behavior and adjusted handgrip strength in post-menopausal women - Alzuwaydi, Aishah; Alshammari, Ghedeir M.; Mohammed, Mohammed A.; Qaisar, Rizwan; Hussain, M. Azhar; Alkahtani, Shaea A. (Frontiers in Nutrition, 2025)
BackgroundThe factors driving the sarcopenia phenotype in post-menopausal women remain partly elusive. We thus investigated the associations of physical activity, sedentary behavior, and metabolic biomarkers with handgrip strength (HGS) as a marker of probable sarcopenia in Saudi post-menopausal women.MethodsWe recruited 268 post-menopausal women aged 50 years or above. Physical activity was assessed using Global Physical Activity Questionnaire (GPAQ), and body composition was measured with a BIA device. Blood samples were used to measure cholesterol and triglyceride levels. Blood pressure and waist circumference (WC) were measured. HGS was measured using a digital HGS dynamometer and an HGS < 16 kg was used to define probable sarcopenia. We applied the ordinary least squares (OLS) regression approach for the dependent variables HGS, HGS relative to skeletal muscle mass (SMM) and HGS relative to fat-to-mass ratio (FMR).ResultsPhysical activity was positively associated with HGS, and sedentary behavior was negatively associated with HGS (p < 0.05). HGS relative to body mass index (BMI) and SMM revealed significant negative relationships with WC (p < 0.05). Taking into account age and FMR, the association with HGS or HGS/SMM existed for physical activity (p < 0.05), sedentary behavior (p < 0.01), and WC (p < 0.001).ConclusionAltogether, we report that high physical activity, low sedentary behavior and low WC are negatively associated with a risk of low HGS among Saudi post-menopausal women.